Analysis of Drug Management in the Pharmaceutical Installation of the South Sorong District Health Office - Endiyonarsi, Endiyonarsi; Uly, Nilawati; Al-Maidin, Achmad R. Muttaqien; Zamli, Zamli (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: The management of pharmaceutical supplies involves a series of coordinated activities related to the planning, procurement, storage, distribution, and disposal of drugs, aimed at ensuring the availability and appropriate use of medications. Objectives: This study aims to describe the implementation pattern of pharmaceutical supply management, focusing on the processes of planning, procurement, and storage at the Pharmacy Installation of the South Sorong Regency Health Office. Methods: A qualitative research design was used, employing in-depth interviews with key informants to gather detailed insights into the procedures and practices involved in pharmaceutical supply management. Results: The planning process is carried out based on the National Formulary and the National Essential Drug List. Drug procurement is conducted annually through E-Purchasing using the Electronic Catalog, following existing national procurement guidelines. The storage system adheres to regulatory standards but is not yet optimized, as drug arrangement is not done alphabetically, which can hinder the efficiency of drug retrieval by personnel. Conclusions:The Pharmacy Installation of the South Sorong Regency Health Office has implemented drug planning, procurement, and storage systems in alignment with national guidelines. However, improvements in drug arrangement and storage optimization are needed to enhance operational efficiency.